Issues and challenges in data collection - suggestions for measuring the creative industries - a regional perspective - Harrison, Philomen (CCS GeorgetownGY, 2006)
Explores some of the resource challenges faced by statistical organizations in the CARICOM region. Provides a synopsis of the approaches that can be used to measure the contribution to the economy of the creative industries.